Аlterationdegree of NMDA and AMPA receptors of glutamate in the pathogenesis of the disease and technological peculiarities of surgical treatment of the hemispheric glioma-swith the epileptic syndrome - V. N. Ochkolyas; M. B. Volov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2014)
The development of effective approaches to the treatment of patients with symptomatic tumor epilepsy was determined by the level of our fundamental knowledge of the basic mechanisms of epileptogenesis on cellular and molecular level. 92 patients with gliomas of the cerebral hemisphereswere examined. Immunoenzyme method ofsemiquantitative determination of the level of autoantibodies to NR2A subunit of NMDA and GluR1 subunit of AMPA receptors of glutamate was used. The reaction of NMDA and AMPA glutamate receptors depending on the availability of an epileptic syndrome in the clinical picture of the disease and the extent of radical surgery has been studied. Pre-emptive increase of the level of autoantibodies to GluR1 subunit of AMPA receptors of glutamate in patients with hemispheric gliomaswith epileptic syndrome was demonstrated. It was foundonly the total removal of the tumor reduced significantly the level of autoantibodies to ionotropic glutamate receptors.